2013
DOI: 10.1021/ic302128q
|View full text |Cite
|
Sign up to set email alerts
|

π-Bonded Dithiolene Complexes: Synthesis, Molecular Structures, Electrochemical Behavior, and Density Functional Theory Calculations

Abstract: The synthesis and X-ray molecular structure of the first metal-stabilized o-dithiobenzoquinone [Cp*Ir-o-(η(4)-C(6)H(4)S(2))] (2) are described. The presence of the metal stabilizes this elusive intermediate by π coordination and increases the nucleophilic character of the sulfur atoms. Indeed, the π-bonded dithiolene complex 2 was found to react with the organometallic solvated species [Cp*M(acetone)(3)][OTf](2) (M = Rh, Ir) to give a unique class of binuclear dithiolene compounds [Cp*Ir(C(6)H(4)S(2))MCp*][OTf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…Indeed in a previous work we investigated the electrochemistry properties of [Cp*Ir‐ o ‐(C 6 H 4 S 2 ‐κ 2 ‐ S , S )] and the related dinuclear complex [Cp*Ir(η‐C 6 H 4 S 2 )IrCp*][OTf] 2 containing a π‐bonded bdt unit. The results demonstrated that the binuclear system becomes more stable and the bdt ligand is less easily oxidized when compared to the mononuclear iridium species [Cp*Ir‐ o ‐(C 6 H 4 S 2 ‐κ 2 ‐ S , S )] . We also notice that higher the conjugation in the C ^ N ligand in complexes 3 – 5 , the easier their reduction is (Table , entries 2–4).…”
Section: Resultsmentioning
confidence: 73%
“…Indeed in a previous work we investigated the electrochemistry properties of [Cp*Ir‐ o ‐(C 6 H 4 S 2 ‐κ 2 ‐ S , S )] and the related dinuclear complex [Cp*Ir(η‐C 6 H 4 S 2 )IrCp*][OTf] 2 containing a π‐bonded bdt unit. The results demonstrated that the binuclear system becomes more stable and the bdt ligand is less easily oxidized when compared to the mononuclear iridium species [Cp*Ir‐ o ‐(C 6 H 4 S 2 ‐κ 2 ‐ S , S )] . We also notice that higher the conjugation in the C ^ N ligand in complexes 3 – 5 , the easier their reduction is (Table , entries 2–4).…”
Section: Resultsmentioning
confidence: 73%
“…The clear characterization of the structure of the complexes supported the elucidation of its possible anticancer mechanisms. 23 Inhibitory Activities of Arene Ru Complexes in Vitro. The antiproliferative activities of the synthetic Ru(II) complexes against various human cancer cell lines and normal MCF-10A human cells were evaluated by using the MTT assay.…”
Section: ■ Materials and Methodsmentioning
confidence: 64%
“…The Ru­(II) atom was bound to the benzene ring, with an average Ru–C distance of 2.183(7) and 2.181(7) Å, whereas the average distance of Ru­(II) to the two chelating nitrogen atoms was 2.089(5) and 2.082(5) Å, respectively. The clear characterization of the structure of the complexes supported the elucidation of its possible anticancer mechanisms …”
Section: Resultsmentioning
confidence: 94%
“…The recognitiono fa romaticm etallacycle stationary points, although unexpected, is not necessarily surprising given the diversec hemistry of aromaticd ithiolene complexes. [40][41][42][43] This is, however,arare example of an aromatic dithiolenem etallacycle coordinating to another metal through its p structure.…”
Section: Photolysis Of [(M-bdt){fe(co) 3 } 2 ]A T85kin Hydrocarbon Mamentioning
confidence: 99%